PUBLIC SERVICES - EFFECTIVE MEANS OF PUBLIC AUTHORITIES FOR SUSTAINABLE DEVELOPMENT - Cliza, Marta Claudia (International Journal of Legal and Social Order, 2024)
Sustainable development has become a more and more common concept in the current background of social, economic, legal realities that concern not only the evolution of Romania in the coming years, but the evolution of the whole humanity. Romania, as a member state of the United Nations (UN) and the European Union (EU), has signed up to the 17 Sustainable Development Goals (SDGs) of the 2030 Agenda, adopted by the UN General Assembly Resolution A/RES/70/1 at the UN Summit on Sustainable Development in September 2015. The EU Council Conclusions, adopted on June 20, 2017, "A sustainable future for Europe: the EU response to the 2030 Agenda for Sustainable Development" is the policy document committed by the EU Member States on the implementation of the 2030 Agenda for Sustainable Development. In this background, each country involved has sought to regulate as best as possible the levers to achieve these goals. This study attempts to answer the question whether public services in Romania and not only, in an improved formula, can represent real mechanisms towards a sustainable development of the society